A stretchable and self-healable all-in-one iontronic elastomer for luminescent caution and multiple perceptions. (17th May 2022) - Zhang, Minjie; Chen, Rong; He, Zixi; Liu, Zhengdong; Dong, Xuemei; Luo, Xu; Song, Cheng; Liu, Juqing
Abstract: Mimicking the multi-functions of biological skin via ionic elastomers is of primary interest for flexible and wearable electronics. Herein, we present a facile all-in-one strategy for preparing highly stretchable and healable iontronic elastomer, being capable of luminescent caution and multimode perception. The all-in-one iontronic elastomer is composed of a phosphor-doped polydimethylsiloxane emitter sandwiched between two solid ionic gel conductors. The all-in-one iontronic elastomer is sensitive to variable stimuli, including tensile, pressure, temperature and liquid. In particular, it shows stable light emission even after stretching up to 250%, bending or twisting 180°, and cut:ting partially. Moreover, the all-in-one iontronic elastomer has been utilized for real-time monitoring of human joint motion and environmental change, as well as signal caution of wearable/portable display, suggesting great potential in personal health and safety care. Graphical abstract: A highly stretchable and healable all-in-one iontronic elastomer that enables functions such as strain, temperature, liquid sensor together with luminescence is developed. Moreover, the multifunctional all-in-one iontronic elastomer can be utilized for real-time monitoring of human joint motion and wearable/portable display. Image 1 Highlights: A liquid free solid ionic gel (SIG) possesses excellent stretchable and self-healable property was prepared. An all-in-one iontronic elastomer was prepared by stacking an electroluminescent layer between two SIGs. The iontronic elastomer exhibits stable light emission under bending, twisting, stretching, or heat treatment states. The iontronic elastomer was utilized for real-time monitoring of human joint motion and wearable/portable display.